Analysis of Factors Affecting Interest in Saving in Sharia Banking in Students of The Madani Nusantara Institute - Ade Ruslan Hidayat; Irsan Apriandinata; Dedi Fatius; Anggie Agustianeu Carolin (SEAN Institute, 2022)
The purpose of this study was to analyze the factors that influence the interest in saving in Islamic Banking in the students of the Madani Nusantara Institute. The method used is descriptive analysis method using a quantitative approach. The population of this research is 5th grade elementary school students in Cibadak Village. While the sample of this study was 60 with as much as 10% of the total population. The instrument used is a questionnaire with 15 items each. The data were analyzed by path analysis with a significance level of = 0.06. The results of this study are that there arethe effect of religiosity on interest in saving of 67.4%, the effect of promotion on interest in saving of 51.6, and the effect of quality of service on interest in saving of 61.1 % while together 66.1% of the variables of interest in saving are influenced byReligiosity , promotion, service quality, while the remaining 33.9% is explained by other variables outside the union.